PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS REALISTIC MATHEMATICS EDUCATION DI MTS NURUL IKHWAN TANJUNG MORAWA - Asyikin, Ainur; Afnaria, Afnaria; Octariani, Dhia (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
Realistic Mathematics Education (RME) is learning mathematics using an approach to everyday problems. Based on the problems in the LKPD used by the teacher, it has not delivered contextual problems that have not provided motivation for students to develop their ideas and experiences. This development research can produce Student Worksheets on the Material of Two Variable Linear Equation Systems. By using the Thiagarajan model which is modified into three stages (Define, Design, Development). This study aims to develop student worksheets based on Realistic Mathematics Education at MTS Nurul Ikhwan Tg. Morawa. The sample is 30 students of class VIII. The research instruments were validation questionnaires, student response questionnaires and tests. Based on several experts, it was obtained as many as 4 people by assessing the assessment with a score of 4.52 in the good category. The practicality results were obtained through a student response questionnaire with a score of 84.8% in the